Two new species of the Colombian endemic genus Allomaieta (Melastomataceae: Cyphostyleae) - Murillo-Serna, Jhon S.; Sierra-Giraldo, Julio Andres; Orozco-A, Jairo Andrés; Posada-Herrera, Juan Mauricio (Phytotaxa, 2025)
Allomaieta is the most diverse genus of the tribe Cyphostyleae (Melastomataceae) and is only known for Colombia. In this contribution two new species of Allomaieta are described and illustrated: Allomaieta melidae and A. peltata. Both grow in the inter-Andean valleys of Central cordillera in the Department of Caldas. Based on their restricted distribution and habitat degradation pressure where these new taxa occur, we present preliminary threat assessments under IUCN guidelines and criteria.